Exploring ukuthunywa as African Methodology: Decolonial research and ethical considerations - Shange, Nombulelo Tholithemba (Critical Studies in Teaching and Learning, 2025)
Western scholars have long viewed themselves as the sole custodians of African experiences, ideals, history, culture, and knowledge. The #RhodesMustFall and #FeesMustFall protests in 2015 and 2016 brought the issue of decolonising knowledge systems to the forefront, encouraging decolonial discourse more suited to the African context. Today, there is a rise in African intellectuals, practices, and solutions, especially in academia, but not much is being done to reimagine and decolonise methodology. This article theorises on African methodologies, which are often overlooked in decolonial discourse. Despite increasing awareness of African indigenous knowledge to address social challenges, these solutions are often accompanied by Western epistemological pedagogies. Ukuthunywa, an important method of passing down useful skills that one still finds in African households today, is theorised in this article. This term loosely translates to ‘being sent to run errands’. The inspiration for this theorising came from a PhD ethnographic study on African healers called Mountain Doctors.